2023
DOI: 10.3389/fmicb.2023.1016872
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in intestinal microbiota and metabolites in individuals with Down syndrome and their correlation with inflammation and behavior disorders in mice

Abstract: The intestinal microbiota and fecal metabolome have been shown to play a vital role in human health, and can be affected by genetic and environmental factors. We found that individuals with Down syndrome (DS) had abnormal serum cytokine levels indicative of a pro-inflammatory environment. We investigated whether these individuals also had alterations in the intestinal microbiome. High-throughput sequencing of bacterial 16S rRNA gene in fecal samples from 17 individuals with DS and 23 non-DS volunteers revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…According to the widely accepted theory of the gut‐skin axis, the mechanism by which the gut microbiota influences acne may be associated with the inflammatory immune response 51 . The abundance of Allisonella is significantly increased in patients with Down syndrome and is positively associated with the levels of proinflammatory cytokines 52 . According to a reported study, Bacteroides were found to stimulate macrophages and monocytes to secrete the proinflammatory cytokine TNFα through an LPS‐mediated pathway 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the widely accepted theory of the gut‐skin axis, the mechanism by which the gut microbiota influences acne may be associated with the inflammatory immune response 51 . The abundance of Allisonella is significantly increased in patients with Down syndrome and is positively associated with the levels of proinflammatory cytokines 52 . According to a reported study, Bacteroides were found to stimulate macrophages and monocytes to secrete the proinflammatory cytokine TNFα through an LPS‐mediated pathway 53 .…”
Section: Discussionmentioning
confidence: 99%
“… 51 The abundance of Allisonella is significantly increased in patients with Down syndrome and is positively associated with the levels of proinflammatory cytokines. 52 According to a reported study, Bacteroides were found to stimulate macrophages and monocytes to secrete the proinflammatory cytokine TNFα through an LPS‐mediated pathway. 53 Medium‐chain triglycerides (MCT) improve the immune status by increasing the abundance of Fusicatenibacter in the intestinal flora.…”
Section: Discussionmentioning
confidence: 99%